2006
DOI: 10.4049/jimmunol.176.2.1252
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Epitope Mimicry in Antiglomerular Basement Membrane Disease

Abstract: Antiglomerular basement membrane (GBM) disease or Goodpasture’s syndrome is among the earliest recognized human autoimmune diseases. Although collagen 4α3 NC1 (Col4α3NC1) has been identified as the responsible autoantigen, it remains unknown how autoimmunity to this autoantigen is provoked. We have demonstrated in our rat model that a single nephritogenic T cell epitope pCol28–40 of Col4α3NC1 induces glomerulonephritis. We hypothesized that microbial peptides that mimic this T cell epitope could induce the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
3
42
0
2
Order By: Relevance
“…Further evidence supporting the role of T cell-mediated cellular immunity in the pathogenesis of EAG is documented in recent studies, including our own, demonstrating that synthetic peptides derived from a3(IV)NC1 can induce glomerulonephritis in Wistar Kyoto (WKY) rats [28][29][30][31][32][33][34][35]. Luo et al showed that a 24-mer synthetic peptide, pCol , from the N terminus of a3(IV)NC1 was capable of inducing glomerulonephritis, although this was mild and inconsistent [29], while Wu et al showed that a 13-mer peptide, pCol (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), containing a T cell epitope from a3(IV)NC1, induced severe crescentic glomerulonephritis [30].…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Further evidence supporting the role of T cell-mediated cellular immunity in the pathogenesis of EAG is documented in recent studies, including our own, demonstrating that synthetic peptides derived from a3(IV)NC1 can induce glomerulonephritis in Wistar Kyoto (WKY) rats [28][29][30][31][32][33][34][35]. Luo et al showed that a 24-mer synthetic peptide, pCol , from the N terminus of a3(IV)NC1 was capable of inducing glomerulonephritis, although this was mild and inconsistent [29], while Wu et al showed that a 13-mer peptide, pCol (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), containing a T cell epitope from a3(IV)NC1, induced severe crescentic glomerulonephritis [30].…”
Section: Introductionsupporting
confidence: 61%
“…In this study we have demonstrated that a 15-mer peptide from the N-terminus of a3(IV)NC1, pCol (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), is recognized by B and T cells from rats immunized with recombinant a3(IV)NC1, and that the same peptide is capable of inducing crescentic glomerulonephritis. Identification of this immunodominant peptide should be of value in designing new therapeutic strategies for mucosal tolerance in EAG, which may be applicable to patients with glomerulonephritis.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations